An ultrasensitive angular interrogation metasurface sensor based on the TE mode surface lattice resonance - Liye Li; Wengang Wu (Microsystems & Nanoengineering)
Abstract The localized surface plasmon resonance metasurface is a research hotspot in the sensing field since it can enhance the light-matter interaction in the nanoscale, but the wavelength sensitivity is far from comparable with that of prism-coupled surface plasmon polariton (SPP). Herein, we propose and demonstrate an ultrasensitive angular interrogation sensor based on the transverse electric mode surface lattice resonance (SLR) mechanism in an all-metal metasurface. In theory, we derive the sensitivity function in detail and emphasize the refraction effect at the air-solution interface, which influences the SLR position and improves the sensitivity performance greatly in the wide-angle. In the measurement, a broadband light source substitutes the single-wavelength laser generally used in traditional angular sensing, and the measured SLR wavelength of broadband illuminant at normal incidence is defined as the single wavelength, avoiding the sensitivity loss from the large angle. The experimental sensitivity can reach 4304.35°/RIU, promoting an order of magnitude compared to those of SPP-sensors. This research provides a novel theory as well as the corresponding crucial approach to achieving ultrasensitive angular sensing.